Penerapan Teknik Bicara Presenter pada Program Siaran Jendela Negeri di TVRI Jakarta - Regi Agriani; R. Hiru Muhammad (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
TVRI Jakarta has a daily program called Jendela Negeri, which airs every morning. The purpose of the Jendela Negeri program is to provide information and understanding about various aspects of Indonesia, thus offering benefits and inspiration to the viewers. The appeal and success of this program are closely linked to the role of the presenter, who has a unique way of delivering information. The presenter hosts the show in a relaxed manner using effective and proper speaking techniques. This study aims to determine the application of the presenter’s speaking techniques and the factors that hinder and support the presenter in conducting the broadcast of the Jendela Negeri program on TVRI Jakarta. This research uses the Presenter Speaking Techniques Theory. It is a qualitative study with a descriptive method. Data collection techniques include in-depth interviews, documentation, and direct observation at TVRI Jakarta. The results indicate that the speaking techniques used by the presenter of the Jendela Negeri program at TVRI Jakarta include seven aspects: tonal range, volume, tempo, rate of delivery, articulation and pronunciation, and diction. The study also identified several obstacles during the broadcast, including technical and non-technical issues such as malfunctioning equipment and inadequate presenter preparation.